Analysis of Physical and Mental Workload Using the Job Strain Index and NASA-TLX Methods on CV. SBRC - Mayasari Tinambunan; Kusnadi Kusnadi; Apid Hapid Maksum (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
Excessive physical and mental activity will lead to consequences in the form of workload. The workload caused by the demands of the job if it is lower than the ability of the worker is likely to cause boredom, on the contrary if the demands of the job are higher than the ability of the worker it will cause fatigue at work. CV. SBRC is a company engaged in the manufacturing industry, namely the production of gloves. Production activities at CV. SBRC is still done manually or by manpower. This study aims to analyze the physical and mental workload of workers on CV. SBRC. The methods used are Job Strain Index and NASA-TLX. Based on the results of this study, the results of the physical workload analysis showed that 9 out of 10 production processes were included in the hazardous category. While the results of the analysis of the mental workload of workers are in the medium category. To overcome activities that fall into the dangerous category, a proposed improvement plan is made for these work activities. Aktivitas fisik dan mental yang dilakukan manusia secara berlebihan akan menimbulkan konsekuensi berupa beban kerja. Beban kerja yang disebabkan oleh tuntutan pekerjaan jika lebih rendah dari kemampaun pekerja kemungkinan akan menimbulkan kebosanan, sebaliknya jika tuntutan pekerjaan lebih tinggi dari kemampuan pekerja maka akan menimbulkan kelelahan dalam bekerja. CV. SBRC adalah perusahaan yang bergerak di bidang industri manufaktur, yakni produksi sarung tangan. Aktivitas produksi pada CV. SBRC masih dilakukan dengan cara manual atau tenaga manusia. Penelitian ini bertujuan untuk menganalisis beban kerja fisik dan mental pekerja pada CV. SBRC. Metode yang digunakan adalah Job Strain Index dan NASA-TLX. Berdasarkan hasil penelitian ini didapatkan hasil analisis beban kerja fisik bahwa 9 dari 10 proses produksi termasuk dalam kategori berbahaya. Sedangkan hasil analisis beban kerja mental pekerja berada dalam kategori sedang. Untuk mengatasi aktivitas yang masuk dalam kategori berbahaya maka dilakukan perancangan usulan perbaikan terhadap aktivitas kerja tersebut.